Novel control strategy for the energy recovery system of a hydraulic excavator - Liu, Changsheng; He, Qinghua; Tang, Qijun; Ren, Kai; Gong, Jun; Zhang, Daqing (International Journal of Agricultural and Biological Engineering, 2024)
The energy saving of hydraulic excavators is always an essential research. An energy recovery system caneffectively recover the boom potential energy and rotational kinetic energy. Based on the standard working cycle of hydraulicexcavators, a dynamic programming (DP) control strategy for hybrid hydraulic excavators was proposed to recover the boompotential energy and rotational kinetic energy. The hybrid hydraulic excavator simulation model was built by Simulinksoftware. The simulation results indicated that the fuel consumption of hybrid hydraulic excavators using the DP controlstrategy was about 21.3% lower than that of the conventional hydraulic excavator. In order to experimentally verify thesimulation results, an experimental platform for hybrid hydraulic excavators was built. The experimental results indicated thatthe fuel consumption of hybrid hydraulic excavators using the DP control strategy was about 18.9% lower than that of theconventional hydraulic excavator. This paper shows that the DP control strategy applied to hybrid hydraulic excavators canrecycle the boom potential energy and rotational kinetic energy, and reduce the fuel consumption of hybrid hydraulicexcavators.Keywords: hybrid excavator, energy recovery, control strategy, simulation analysis, test platformDOI: 10.25165/j.ijabe.20241702.7774Citation: Liu C S, He Q H, Tang Q J, Ren K, Gong J, Zhang D Q. Novel control strategy for the energy recovery system of a hydraulic excavator. Int J Agric & Biol Eng, 2024; 17(2): 94–101.